Study of essential hypertension with special reference to end organ damage in adults - M., Rukmini Ramya; M., Rajya Lakshmi (International Journal of Advances in Medicine, 2018)
Background: Hypertension, a major public health concern, affecting 20-25% of the adult population. It is the major risk factor for diseases involving Cardio Vascular (CV) and renal system. The World Health Organization (WHO) has estimated that high Blood Pressure (BP) causes 1 in every 8 deaths, making hypertension the third leading killer in the world. The recent emerging trend in the treatment of hypertension is not only based on the pragmatic need to lower BP levels, but also on lowering the CV risk profile, which is largely linked to the presence of the end organ damage. Methods: One hundred patients with hypertension are recruited in this study. The ethics committee of Rangaraya Medical College, Kakinada approved this study and all the participants provided informed consent for all the procedures in the study protocol. Results: Majority of the patients (40%) with EOD have hypertension of >10 years duration. The relative frequency of various end organ damages (CVS: 34%, CNS: 17%, kidney: 12% and eye: 10%) is also high in patients with hypertension of >10 years duration. Conclusions: A significant proportion of hypertensive subjects had documented associated EOD, with LVH being the most prevalent EOD. The above findings emphasize the important role of the primary care clinicians to the early detection, treatment and control of high blood pressure that might help to reducing overall cardiovascular risk.